Five power defence arrangements at forty - Storey, Ian, 1970- 532830; Emmers, Ralf, 1974- 532831; Singh, Daljit 327055; S. Rajaratnam School of International Studies 532832; Institute of Southeast Asian Studies 8280 (Singapore : Institute of Southeast Asian Studies, 2011)
Includes bibliographical references and index